Enhanced volatile fatty acids production from anaerobic fermentation of grease trap waste by Fenton pretreatment - Rui Miao; Yongxia Liu; Minghui Zhang; Jialin Wan; Zhangwei He; Baoshan Xing; Danxi Huang; Lei Wang (Water Cycle)
To achieve the efficient reclamation of organic resources in grease trap waste (GTW), a Fenton pretreatment for GTW was proposed in this work to convert the organic resources in GTW to soluble chemical oxygen demand (SCOD), followed by SCOD was then degraded into volatile fatty acids (VFAs) via anaerobic fermentation. The effects of the reaction conditions, H2O2 and Fe2+ dosages during Fenton pretreatment on the properties of GTW were investigated, and the yield and composition of VFAs were evaluated. The results showed that the grease and organic matter in GTW were mostly present as oil droplets and solid particles; thus, the system needed to be stirred vigorously after adding H2O2 to ensure full contact of H2O2 with the grease and organic molecules. Then, Fe2+ was added to initiate the Fenton reaction to change the properties of GTW. When the dosages of H2O2 and Fe2+ were 2% and 300 mg/L, respectively, the SCOD of GTW after Fenton pretreatment increased by 256%, the viscosity decreased by 99%, and the oil content decreased from 37% to 3%. These results indicated that Fenton pretreatment provided better organic matter and mass transfer conditions for anaerobic fermentation. The VFAs yield in the stable operation stage reached 19,059–21,999 mg/L.